DESIGN AND PERFORMANCE ANALYSIS OF SOLAR PARABOLID DISH CONCENTRATOR SYSTEM FOR PROCESS HEATING - Uppal, Anubhav; Kesari, Dr. J P; Mishra, Dr. R S (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Indian industry is under tremendous pressure to make their products more environmentally sound. Not only the products themselves, but also the whole production process has to become more sustainable to Achieve India’s pledge to stop climate change at world forum. The Indian industry is one of the major sectors in India which have very high share in India’s Gross Domestic Product (GDP) with annual share of 25% in 2015-2016. Also Indian industry has huge energy requirements in the form of both thermal and electrical energy. Manufacturing of final components and their sub components involves many steps such as casting, forging, and painting and electroplating etc that require thermal energy in form of hot air, water or steam. Thermal energy requirement accounts for around 70% of all India industry’s total energy consumption. Max thermal energy requirement is well below 200°C and solar thermal collectors can provide a large share of this industrial process heat demand easily. The solar thermal collector technology used depends upon a great deal on the temperature levels involved. The use of an appropriate solar thermal technology can have a positive impact on the energy and environmental scenario of Indian industry at a large. There are various solar thermal technologies including CST technologies that are available for Indian industries